2016
DOI: 10.1590/0034-7167.2016690323i
|View full text |Cite
|
Sign up to set email alerts
|

Tecnologias educativas para promoção do (auto) cuidado de mulheres no pós-parto

Abstract: Objective: to evaluate national and international literature regarding the use of educational technologies to encourage self care in postpartum women. Method: an integrative review of the literature. The articles were collected from the CINAHL, SCOPUS, PubMed, SciELO, LILACS and Cochrane databases; the time period for the articles referred to January/2004 to July/2014; the languages used in the articles were Portuguese, English, Spanish and French; the articles were selected from the following descriptors: pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
0
15
0
13
Order By: Relevance
“…In the evolution of health care and in the context of nursing care, these different types of technologies are developed through the need to translate technical-scientific knowledge into tools, processes, and materials. Studies have shown that together, these elements not only improve quality of care, but also expand possibilities for nurses when carrying out care producing practices (10) . Among existing technologies, educational ones refer to the group of strategies that aim to innovate education, used by educators and educatees, in the various methods of formal-academic and formal-ongoing learning (11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…In the evolution of health care and in the context of nursing care, these different types of technologies are developed through the need to translate technical-scientific knowledge into tools, processes, and materials. Studies have shown that together, these elements not only improve quality of care, but also expand possibilities for nurses when carrying out care producing practices (10) . Among existing technologies, educational ones refer to the group of strategies that aim to innovate education, used by educators and educatees, in the various methods of formal-academic and formal-ongoing learning (11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…The second part of the instrument was composed of items that assessed all subjects in a more detailed way, being adapted from Barbosa, where, for each topic covered, the judges answered "yes" or "no" as to clarity, comprehension and relevance, and, lastly, the degree of suitability (1-inadequate, 2-partially adequate, 3-adequate, 4-fully adequate). 20 After the evaluation, the CI was applied to assess the proportion of judges in agreement on the aspects contained in the instrument, related to content and appearance; the items with concordance >or=0.78 were considered adequate. [21][22] To quantify the level of agreement in relation to the second part of the instrument, those that reached an index equal to or greater than 80% were considered valid.…”
Section: Internal Validationmentioning
confidence: 99%
“…[21][22] To quantify the level of agreement in relation to the second part of the instrument, those that reached an index equal to or greater than 80% were considered valid. 20 On the other hand, the judges of communication used an instrument adapted from Doak, Doak and Root 23 , Suitability Assessment of Materials -SAM, evaluating the suitability of the book based on the aspects related more specifically to this professional category, such as: layout and presentation, language, graphic illustrations, motivation and cultural adequacy. According to this instrument, each evaluated item receives a score, being "0" (inadequate), "1" (partially adequate) or "2" (adequate).…”
Section: Internal Validationmentioning
confidence: 99%
“…Thus, the authors emphasize the importance of the use of educational technologies by health professionals to help these women adapt themselves to the new role (18).…”
Section: Educational Strategies For Self-care and Care For The Babiesmentioning
confidence: 99%
“…This strategy has been incorporated into the activities of the pregnant women's groups and was well received by the participants. On the other hand, it is known that these pregnant teenagers are strongly influenced by their family culture (15,18).…”
Section: Girls Who Are Expecting Their First Babies Should Attend Thementioning
confidence: 99%